We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
957
5
avatar

integral of xe^square root of x dx

 Nov 29, 2014

Best Answer 

 #1
avatar+105683 
+13

 

After the substitution step I have used integration by parts 3 seperate times - How about that!

 

$$\\INTEGRATION BY PARTS\\\\
\boxed{\int uv'\;dx= uv-\int\;vu' \;dx}$$

 

$$\begin{array}{rllll}
\int x e^{\sqrt{x}}dx&=&\int\frac{2\sqrt{x}\;x\;e^{\sqrt{x}}}{2\sqrt{x}}\;dx\qquad\qquad &\left[\frac{d}{dx}x^{1/2}=\frac{1}{2}x^{-1/2}=\frac{1}{2\sqrt{x}}\right]\\\\
&=&2\int\frac{(\sqrt{x})^3e^{\sqrt{x}}}{2\sqrt{x}}\;dx\qquad\qquad &\\\\
&&&let\;t=\sqrt{x}\\\\
&&&\;dt=\frac{1}{2}x^{-1/2}dx=\frac{1}{2\sqrt{x}}dx\\\\
&=&2\int t^3e^tdt\qquad\qquad &\\\\
&=&2\left[t^3e^t-\int3t^2e^tdt\right] \qquad\qquad &u=t^3\quad v'=e^t\\
&& \qquad\qquad &u'=3t^2\quad v=e^t\\
&=&2t^3e^t-6\int t^2e^tdt \qquad\qquad &\\\\
&=&2t^3e^t-6\left[t^2e^t-\int 2te^tdt\right] \qquad\qquad &u=t^2\quad v'=e^t\\
&& \qquad\qquad &u'=2t\quad v=e^t\\
\end{array}$$

 

$$\begin{array}{rllll}
\int x e^{\sqrt{x}}dx &=&2t^3e^t-6t^2e^t+12\int te^tdt\right]\\\\
&=&2t^3e^t-6t^2e^t+12\left[te^t-\int e^t dt\right] \qquad\qquad &u=t\quad v'=e^t\\
&& \qquad\qquad &u'=1\quad v=e^t\\
&=&2t^3e^t-6t^2e^t+12te^t-12e^t+k\\\\
&=&2e^t\left[t^3-3t^2+6t-6\right]+k\\\\
&=&2e^{\sqrt{x}}\left[(\sqrt{x})^3-3(\sqrt{x})^2+6(\sqrt{x})-6\right]+k\\\\
&=&2e^{\sqrt{x}}\left[x^{3/2}-3x+6(\sqrt{x})-6\right]+k\\\\
\end{array}$$

.
 Nov 29, 2014
 #1
avatar+105683 
+13
Best Answer

 

After the substitution step I have used integration by parts 3 seperate times - How about that!

 

$$\\INTEGRATION BY PARTS\\\\
\boxed{\int uv'\;dx= uv-\int\;vu' \;dx}$$

 

$$\begin{array}{rllll}
\int x e^{\sqrt{x}}dx&=&\int\frac{2\sqrt{x}\;x\;e^{\sqrt{x}}}{2\sqrt{x}}\;dx\qquad\qquad &\left[\frac{d}{dx}x^{1/2}=\frac{1}{2}x^{-1/2}=\frac{1}{2\sqrt{x}}\right]\\\\
&=&2\int\frac{(\sqrt{x})^3e^{\sqrt{x}}}{2\sqrt{x}}\;dx\qquad\qquad &\\\\
&&&let\;t=\sqrt{x}\\\\
&&&\;dt=\frac{1}{2}x^{-1/2}dx=\frac{1}{2\sqrt{x}}dx\\\\
&=&2\int t^3e^tdt\qquad\qquad &\\\\
&=&2\left[t^3e^t-\int3t^2e^tdt\right] \qquad\qquad &u=t^3\quad v'=e^t\\
&& \qquad\qquad &u'=3t^2\quad v=e^t\\
&=&2t^3e^t-6\int t^2e^tdt \qquad\qquad &\\\\
&=&2t^3e^t-6\left[t^2e^t-\int 2te^tdt\right] \qquad\qquad &u=t^2\quad v'=e^t\\
&& \qquad\qquad &u'=2t\quad v=e^t\\
\end{array}$$

 

$$\begin{array}{rllll}
\int x e^{\sqrt{x}}dx &=&2t^3e^t-6t^2e^t+12\int te^tdt\right]\\\\
&=&2t^3e^t-6t^2e^t+12\left[te^t-\int e^t dt\right] \qquad\qquad &u=t\quad v'=e^t\\
&& \qquad\qquad &u'=1\quad v=e^t\\
&=&2t^3e^t-6t^2e^t+12te^t-12e^t+k\\\\
&=&2e^t\left[t^3-3t^2+6t-6\right]+k\\\\
&=&2e^{\sqrt{x}}\left[(\sqrt{x})^3-3(\sqrt{x})^2+6(\sqrt{x})-6\right]+k\\\\
&=&2e^{\sqrt{x}}\left[x^{3/2}-3x+6(\sqrt{x})-6\right]+k\\\\
\end{array}$$

Melody Nov 29, 2014
 #2
avatar+104963 
+5

Very clever, Melody........that initial "trick" of mutiplying the top and bottom by  2√x  was the key, wasn't it....???....I could have looked for hours and never discovered that......

(Maybe I should have bought some Coronas, too!!)

 

 Nov 29, 2014
 #3
avatar+105683 
+5

Yes maybe you should have    

 Nov 29, 2014
 #4
avatar+104963 
0

Smart aleck.......

 

 Nov 29, 2014
 #5
avatar+28208 
+10

Here's an alternative method:

integration

.

 Nov 29, 2014

17 Online Users

avatar